(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence of exposure to e-cigarette advertising and identify associated factors among first-year students at Hanoi Medical University in 2024. Methods: A cross-sectional descriptive study was conducted among 457 first-year medical students from 11/2023 to 6/2024. Results: The study indicated that two-thirds of first-year students (67.0%) reported exposure to e-cigarette advertising, with social media being the primary channel. Students who had acquaintances using e-cigarettes were more likely to be exposed to e-cigarette advertising compared with those who did not (OR = 1.6; 95% CI: 1.1–2.4; p = 0.026). In addition, students who were exposed to e-cigarette smoke in the past 30 days were also more likely to encounter e-cigarette advertising than those who were not exposed (OR = 1.9; 95% CI: 1.2–2.9; p = 0.04). Conclusions: A high prevalence of exposure to e-cigarette advertising was observed among first-year students at Hanoi Medical University, with social media being the most common source of exposure. A statistically significant association was found between exposure to e-cigarette advertising and both having acquaintances who use e-cigarettes and passive exposure to e-cigarette smoke in the past 30 days.